2017
DOI: 10.1177/0003122417735742
|View full text |Cite
|
Sign up to set email alerts
|

The Decline and Persistence of the Old Boy: Private Schools and Elite Recruitment 1897 to 2016

Abstract: Abstract:We draw on 120 years of biographical data (N = 120,764) contained within Who's Who-a unique catalogue of the British elite-to explore the changing relationship between elite schools and elite recruitment. We find that the propulsive power of Britain's public schools has diminished significantly over time. This is driven in part by the wane of military and religious elites, and the rise of women in the labor force. However, the most dramatic declines followed key educational reforms that increased acce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 72 publications
1
71
0
4
Order By: Relevance
“…However, even then family influence over first jobs for future economic elites had declined relative to chairmen born in the nineteenth century (Stanworth and Giddens : 91). In line with larger studies of the elite (Reeves et al ) that have shown the declining influence of attending an elite ‘Clarendon’ school or Oxbridge, Davis () has recently suggested that education and particularly professional business education such as an MBA is increasingly important compared to attending older elite universities. Our study is in the unique position of being able to look comprehensively at the role of education and other factors in recruitment into the most prestigious firms of British finance and consultancy as it happens .…”
Section: Introduction: Higher Education Prestige Employers and Elitementioning
confidence: 79%
“…However, even then family influence over first jobs for future economic elites had declined relative to chairmen born in the nineteenth century (Stanworth and Giddens : 91). In line with larger studies of the elite (Reeves et al ) that have shown the declining influence of attending an elite ‘Clarendon’ school or Oxbridge, Davis () has recently suggested that education and particularly professional business education such as an MBA is increasingly important compared to attending older elite universities. Our study is in the unique position of being able to look comprehensively at the role of education and other factors in recruitment into the most prestigious firms of British finance and consultancy as it happens .…”
Section: Introduction: Higher Education Prestige Employers and Elitementioning
confidence: 79%
“…Britain's aristocracy were certainly embattled by piecemeal reform and economic shocks in this period, but they did not face the kind of violent revolutions or wholesale expropriation of elite institutions that so profoundly altered elite culture in countries like France and Germany (Cannadine 1999). Instead, the structure of the British elite-in terms of both its occupational makeup and the schools and universities from which it has traditionally recruited its members-stayed remarkably stable over time (Reeves et al 2017). The British case, then, provides a unique lens on elite cultural change that is far less muddied by abrupt ruptures in the ruling classes or by radical reconfigurations of elite institutions.…”
Section: Stable and Expansive: The Case Of The British Elitementioning
confidence: 99%
“…Educational systems cross-nationally may play a crucial role in structuring the distribution of cultural capital (embodied and institutionalized) and determining the convertibility of cultural consumption (Bourdieu 1986). In the UK, it is not uncommon to find both bankers and journalists, stockbrokers and academics attending the same schools and universities, and even studying the same subjects (Reeves, Friedman, Rahal and Flemmen 2017). Not only do alumni share similar credentials but the common form of embodied cultural capital acquired during these school years actually expands their career options.…”
Section: Discussionmentioning
confidence: 99%